2022
DOI: 10.1093/nutrit/nuac060
|View full text |Cite
|
Sign up to set email alerts
|

Effects of conjugated linoleic acid and exercise on body composition and obesity: a systematic review and meta-analysis

Abstract: Context Conjugated linoleic acid (CLA) has been reported to have anti-obesity and antidiabetic effects. However, the benefits of CLA combined with exercise remain unclear, and studies report conflicting results. Objective A systematic review and meta-analysis were performed to investigate the synergistic effect of CLA and exercise on body composition, exercise-related indices, insulin resistance, and lipid profiles; and of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Also, a recent meta-analysis demonstrated an improvement in anthropometric parameters and body composition after CLA supplementation in adults ( 36 ). However, Liang et al ( 21 ), in their meta-analysis, demonstrated that CLA supplementation during exercise programs did not improve body weight but significantly reduced fat mass. Taking into account the inconsistency in the obtained results we hypothesized that psychological factors might affect the success of the CLA intervention and ability to complete the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, a recent meta-analysis demonstrated an improvement in anthropometric parameters and body composition after CLA supplementation in adults ( 36 ). However, Liang et al ( 21 ), in their meta-analysis, demonstrated that CLA supplementation during exercise programs did not improve body weight but significantly reduced fat mass. Taking into account the inconsistency in the obtained results we hypothesized that psychological factors might affect the success of the CLA intervention and ability to complete the study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect was small and did not seem clinically relevant. Contrary, Liang et al ( 21 ) in a recent meta-analysis demonstrated that CLA supplementation during exercise programs was not effective for body-weight control compared to exercise alone but significantly reduced fat mass.…”
Section: Introductionmentioning
confidence: 94%
“…In 7 articles (7 claims) the effect was stated to be larger in one group, but the overall differences were not statistically significant [33,[70][71][72][73][74][75]. 3 articles (3 claims) had different forms of fallacies: a p-value of 0.09 was considered significant [76];…”
Section: Fallacious Claimsmentioning
confidence: 99%